Acute medullary ischemia as clinical presentation of an intact infrarenal abdominal aortic aneurysm - Nicola Troisi, PhD; Valentina Scarati, MD; Giulia Bertagna, MD; Raffaella Berchiolli, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
Abdominal aortic aneurysms (AAAs) are usually asymptomatic. Abdominal and/or low back pain are signs of rupture or impending rupture. We report the case of an 88-year-old man with unusual symptoms of clinical presentation for an AAA. He was admitted to our hospital with low back pain associated with bilateral lower extremity paresis. Examination revealed an abdominal pulsatile mass, and palpable peripheral pulses. Computed tomography angiography detected a 65-mm intact infrarenal AAA with neither signs of fissure or rupture nor lower extremity arterial disease. Magnetic resonance imaging demonstrated low-intensity signals at L1-L2 in the middle of the conus medullaris (acute medullary ischemia). The patient was managed conservatively with monoantiplatelet therapy, and low-weight-molecular heparin. Symptoms were resolved completely after 3 days. The final decision was to not treat the AAA.